SMOOTH MUSCLE RELAXANT ACTIVITY OF A DIHYDROPYRIMIDINE DERIVATIVE 5-ACYL-6-METHYL-4-PHENYL-2-S-ETHYL-1, 4-DIHYDROPYRIMIDINE (BK- VI) ON ISOLATED RAT UTERUS AND RABBIT AORTIC STRIP. - salwan, poonam; salwan, Shalini (Journal of Drug Delivery and Therapeutics, 2012)
ABSTRACT Objective: To investigate the smooth muscle relaxant activity of a newly synthesized dihydropyrimidine derivative 5-acyl-6-methyl-4-phenyl-2-S-ethyl-1,4-dihydropyrimidine (BK- VI) and nifedipine on isolated rat uterus and rabbit aortic strip. Material and Methods: Effect of the test compound BK-VI on the smooth muscles of isolated rat uterus and isolated rabbit aortic strip was observed and compared with that of nifedipine. Observations were made with increasing bath concentrations of BK-VI and nifedipine.Six preparations were used for each dose of BK-VI and nifedipine.Mean effect of increasing doses of BK-VI and nifedipine on the height of calcium-induced contraction of depolarized isolated rabbit aortic strip and on K+-induced contraction of isolated rat uterus were noted and IC-50 calculated. Results: Test compound BK-VI had a significant dose-dependent relaxant effect on K+-induced contractions of isolated rat uterus. Significant relaxation was seen at bath concentration starting from 9.34x10-4M (IC-50=12.2x10-4M).Nifedipine showed significant relaxation at all bath concentrations starting from 2.8X10-7M(IC50=7.5X10-7M).Compound BK-VI produced potentiation of Ca2+-induced contractions of K+-depolarized rabbitâ€™s aortic strip at bath concentration of 0.7Ã—10-5M while significant inhibition was observed at higher bath concentrations. Nifedipine showed dose-dependent significant inhibition at all bath concentrations. Conclusion: BK-VI has a calcium channel blocking activity like nifedipine and it can inhibit the Ca2+ dependent contractions of smooth muscles of uterus and aorta. KEY WORD: Calcium channel blockers, Dihydropyrimidines, Voltage dependent calcium channels.